Challenges of Using Artificial Intelligence in Human Capital Management at the Communications, Space, and Technology Commission in the Kingdom of Saudi Arabia - Alotaibi, Ahlam Melfi (Journal of Economic, Administrative and Legal Sciences, 2025)
Due to evolving business environments and heightened competition, human capital management (HCM) is encountering new challenges in adopting advanced digital technologies like artificial intelligence (AI), necessitating a delicate balance between addressing these challenges and promoting organizational growth and development. The objective of this research is to pinpoint the challenges encountered when utilizing AI technologies in HCM within the Saudi Communications, Space, and Technology Commission (CST). This study utilizes a qualitative method that includes a literature review on the subject. The results showed various challenges hindering the implementation of AI in HCM on a global scale, which can be categorized into methodological, societal, and technological challenges. In the Saudi context, and within the CST, five main challenges of using AI in HCM were identified, including data privacy, data security, automation, social acceptance, and lack of professional competencies. According to the results of this research, it can be inferred that utilizing AI technology in HCM, if done properly, has the potential to unlock featured opportunities at the CST. It is recommended to conduct further research on developing a feasible framework for incorporating AI into HCM.
Keywords: Communications Space and Technology Commission; human capital management; Saudi Arabia; Artificial intelligence; challenges